Markers of renal function at admission and mortality in hip fracture patients - a single center prospective observational study. (3rd May 2021) - H. Jonsson, Magnus; Åkesson, Anna; Hommel, Ami; Grubb, Anders; Bentzer, Peter
Abstract: Plasma cystatin C and shrunken pore syndrome (SPS) are associated with increased mortality in older adults. The objective was to assess the association between these markers of kidney function at admission and mortality in hip fracture patients. Hip fracture patients presenting at Lund University Hospital were eligible for inclusion. Cox regression was used to assess association between plasma cystatin C, creatinine, cystatin C- or creatinine-based estimations of glomerular filtration rate (eGFRCYS and eGFRCREA ), or SPS (defined as eGFRCYS /eGFRCREA < 0.7) and mortality during one year follow up. Improvement in discrimination relative to the Nottingham Hip fracture score was assessed by Receiver Operational Characteristics (ROC) analysis and calculation of Net Reclassification Index (NRI). 996 patients were included in the study. Cystatin C, creatinine, eGFRCYS and eGFRCREA were associated with one-year mortality in both unadjusted and adjusted analyses. The association with mortality was stronger for cystatin C and for eGFRCYS than for creatinine and eGFRCREA . Patients with SPS had doubled mortality compared with patients without SPS (43.7 and 20.2%, respectively, p  < .001). Hazard ratio for SPS in the adjusted analysis was 1.66 (95%CI; 1.16–2.39, p  = .006). None of the markers improved discrimination compared to the Nottingham Hip Fracture Score using ROC analysis whereas eGFRCYS and eGFRCREA improved NRI. Our conclusion is that plasma concentrations of creatinine or cystatin C, eGFRCYS or eGFRCREA or SPS at admission in hip fracture patients are associated with mortality when known risk factors are accounted for. Identification of high risk patients may be improved by eGFRCYS or eGFRCREA .